(3TQM eG jbY ajg GdJUMja hGdJMQjas - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO Hf jMji Hf egQGf, CHh gdGd GdYScQj , J (B395 (3g` s
(3ChdgG (B:s
(3GdMeO ddg cKjQkG ceG gh Cgdg hai GdTYQGA KdGKg Sehf GdeaUd hdjShG ef GdeaUd Hf eMeO GdVHi ai TF efge s
(3BNQgG (B:s
(3bGd eG CYde ajgG EdG eG bVi Ydi hUdi Gddg Ydi eMeO hBdg hSde s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B560s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3COH (B194) s
Keywords: (3GddZIs